Factors Contributing to the Implementation of Situational Leadership in Hospitals - Heryyanoor, Heryyanoor; Nursalam, Nursalam; Hidayat, Abdul Aziz Alimul; Raziansyah, Raziansyah; Rusdiana, Rusdiana; Hasaini, Asni (International Journal of Psychosocial Rehabilitation, 2020)
An organization’s success in achieving its goals is influenced by the leader. But in carrying out its leadership, leaders often experience obstacles from various factors. This study aimed to consider factors that influence the application of situational leadership in hospitals. A cross-sectional quantitative research design was used with a population of 162 nurses and a sample of 115 nurses. The independent variables were leader internal factors, nurse factors, job characteristics; and the independent variable was situational leadership. The instrument was in the form of a questionnaire related to the internal factor variables of the leader: 25 questions, the factor of nurses: 13 questions, job characteristics: 10 questions, and situational leadership: 32 questions. Multivariate analysis with multiple linear regression tests was used. There was a joint effect of internal leader factors, nurse factors and job characteristics on the application of situational leadership with a value of p = 0.000 (p <0.00) and R Square 0.437 (43.7%) where the dominant factor was the nurse factor. The results of the analysis of multiple linear regression tests obtained a significance value of internal factors leader of p = 0.000 (p <0.05); nurse factor p = 0.000 (p<0.05); and job characteristics p = 0.601 (p> 0.05). Internal leadership factors and nurse factors influence the application of situational leadership while job characteristics do not affect it. Influential factors are used as the basis for implementing situational leadership in hospitals referring to aspects of increasing nurses’ knowledge and expectations.